La democratización del espectro radioeléctrico y sus efectos en los medios de comunicación radiales privados de la ciudad de Loja - Pizarro Giron, Teresa Micaela (2015)
With this research the knowledge among media owners private radio communication of the town, on the democratization of the radio spectrum raises the Communications Law, strengthening the equitable distribution of radio frequencies and the faithful fulfillment of it was determined by existing radios, offering quality information and programs with positive social impact, in accordance with principles of participation, intercultural, plurinational and transparency. The private sector has some discomfort to feel disadvantaged with new enforcement of the law regarding the distribution of radio frequencies, because the private sector has 75% of frequencies presently it aims to balance equally in public, private and community sectors, through the "SUPERCOM" and make constant monitoring, without missing any contravention to impose sanctions on owners of radios. This research was conducted in the period September 2013 to July 2014, gathering concerns, direct and critical information about the Communications Law and the democratization of the radio spectrum. Quantitative and qualitative methods applied, collecting secondary data and primary data through surveys and interviews, which allowed them to better analyze the democratization of the radio spectrum; the information collected 197 respondents and two respondents, then you have enough information on the subject of study and have the opinion of citizens is proposed to conduct a radio program of interaction of learning for children, the same that will help because it will be a 100% Education program, also contribute to the intellectual and psychomotor development of children in the city of Loja, after the corresponding appreciation ask the SUPERCOM the broadcast on the radio public. This will be fulfilling the law which refers to the democratization of the radio spectrum and use with a social and educational purpose, aimed at a significant population segment. Keywords: Democratization, radio spectrum, media, private radio stations.